2003
DOI: 10.1629/16191
|View full text |Cite
|
Sign up to set email alerts
|

The growth and number of journals

Abstract: The number and the growth characteristics of scholarly journals have been matters of some debate for a considerable time. Many assumptions about the future of the scholarly communication system have been predicated on very high estimates of the number of journal titles and their seemingly inexorable growth. This article argues in favour of a novel approach to estimating journal numbers and provides results that are consistent with other lines of enquiry. An analysis of the results also allows a model of journa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
1
15

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 3 publications
3
85
1
15
Order By: Relevance
“…For newcomers to the field, it is hard to establish a baseline understanding of seminal work. New journals are popping up on a regular basis [27]. Good recommender systems can play a valuable role in winnowing down publications of interest.…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For newcomers to the field, it is hard to establish a baseline understanding of seminal work. New journals are popping up on a regular basis [27]. Good recommender systems can play a valuable role in winnowing down publications of interest.…”
Section: Background and Related Workmentioning
confidence: 99%
“…For example, citation databases are often incomplete, and have issues disambiguating homographs. They may also be subject to the Matthew Effect [21], [27] which is the sociological phenomenon that eminent scientists will often get more credit than a comparatively unknown researcher, even if their work is similar. Textbased recommenders often have trouble with synonyms and context-based words, and often cannot identify papers that may be related.…”
Section: Background and Related Workmentioning
confidence: 99%
“…This means that the number of active journals has been doubling every 20 years." 4 While this growth rate might have been reasonably sustainable for the better part of those three centuries, libraries were dealing with an additional problem beginning with the 1980s and 1990s. Not only were libraries grappling with an increased number of journal titles, they were also dealing with the price of In 1993, a Library Journal survey found that 80% of public libraries and 99% of academic libraries offered their patrons access to electronic resources.…”
Section: Historymentioning
confidence: 99%
“…Thereafter, research spending fell back to a growth rate of about 3% a year, as did the literature. 1 The driving force behind the growth in the journal literature appears to be the rate of specialization of knowledge, rather than anything that publishers or librarians do.…”
mentioning
confidence: 99%